Variability of Agro-morphological Character and Genotype Clustering of Watermelon [Citrullus lanatus (Thunberg) Matsum & Nakai] as Basic Selection for New Variety - Lestari, Puji; Waluyo, Budi (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2022)
Watermelon [Citrullus lanatus (Thunb) Matsum Nakai] is an important fruit commodity, which has the potential to be developed. Watermelon belongs to the cucurbitaceae family, which has advantages in terms of nutritional, environmental and economic values. Production of watermelon in Indonesia decreased from 2014 to 2016. Therefore, the productivity of watermelons could be increased by conducting this research. The aim of this research was to examine the variability of agro-morphological characters and clustering of watermelon. This research was conducted using seventy eight watermelon genotypes. Seventy-five watermelon genotypes and three commercial varieties were grown in an augmented design. Seventy-five genotypes were spread into four blocks, and each block contained the commercial varieties. The result of this research showed that the cumulative variability reached 81.22 %, with seventen main components and only five effective main components. Based on the cluster analysis, the seventy eight watermelon genotypes were divided into seven clusters, resulting in genetic distance of 0.486 - 0.999 and coefficient of similarity of 93 %. Ten watermelon genotypes selected based on consumer preferences can be used as recommendations to be released as a variety.